Pre-prosthetic Schuchardt Osteotomy: The contribution of computer-assisted surgical planning - Samama Mickaël; Masliah Julia (EDP Sciences, 2024)
Premature loss of teeth leads to an inevitable egression of opposing teeth. Schuchardt osteotomy is a quick and efficient alternative to create a prosthetic space compatible with prosthetic rehabilitation. Its planning and execution are now facilitated by the rise of digital technology and specialized softwares. Through virtual simulation of the osteotomy and the creation of surgical guides, they offer enhanced safety and predictability. Communication between the practitioner and the laboratory, as well as between the practitioner and the patient, is strengthened. In this clinical case, we will detail the key steps in digital planning, and the surgical protocol for a segmental Schuchardt osteotomy for preprosthetic purposes.